Kuwait : 2011 Article IV Consultation: Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Kuwait. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Kuwait faced the global financial crisis from a position of strength, owing to expansionary fiscal stance. The economy is expected to grow steadily over the medium term as Kuwait continues to implement the development plan and global recovery supports demand for oil. The near-term macroeconomic policy mix is adequate. The development plan (DP) implementation should be managed carefully. The financial situation of many investment companies remains precarious. Significant progress was made in the implementation of the update recommendations, but further steps are warranted.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet